Simple construction of GdBiVO4 assembled on reduced graphene oxide for selective and sensitive electrochemical detection of chloramphenicol in food samples. (23rd December 2021) - Gopi, Praveen Kumar; Srinithi, Subburaj; Chen, Shen-Ming; Hunsur Ravikumar, Chandan
Abstract : In the present study, the influence of phase purity and crystallinity on the electrochemical properties of well-designed GdBiVO4 @rGO nanocomposite, fabricated by the facile hydrothermal method for the detection of chloramphenicol (CP), is reported. Abstract : In the present study, the influence of phase purity and crystallinity on the electrochemical properties of well-designed GdBiVO4 @rGO nanocomposite, fabricated by the facile hydrothermal method for the detection of chloramphenicol (CP), is reported. The surface morphology and electrochemical sensing property of as-prepared samples were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron microscopy, UV-visible diffuse reflectance spectroscopy and electron impedance spectroscopy techniques. The electrochemical property of synthesized GdBiVO4 @rGO nanocomposite was used for the detection of hazardous antiprotozoal CP drug in food, scrutinized by cyclic voltammetry and differential pulse voltammetry. The GdBiVO4 @rGO nanocomposite on an electrode showed an excellent and quick response towards CP drug. Under an optimized condition, the proposed electrochemical sensor displayed a low detection limit of up to 0.0229 μM and broad linear range of 0.05–36.55 and 42.55–2336.55 μM for CP. In addition, the GdBiVO4 @rGO electrodes exhibited good performance characteristics of repeatability and reproducibility and proved suitable for CP analysis in food samples.